Analysis of Competency Factors Affecting the Performance of Laboratory Staff About Plebhotomy at UPT. Medan Regional Health Laboratory Center in 2019 - Farida Fransisca Sihotang; Ayi Darmana; Tarsyad Nugraha (Newinera Publisher, 2020)
Performance is the work achieved by a laboratory officer in carrying out its functions in accordance with the responsibilities assigned to it by following the rules applicable in the laboratory. The purpose of this study was to determine the effect of training, documentation, and skills on laboratory staff performance about phlebotomy in UPT. Medan Regional Health Laboratory Center in 2019. This study used a quantitative type with a cross-sectional design. The research was conducted at UPT. Medan Regional Health Laboratory Center in 2019. The data collected is primary data with a questionnaire tool. The informants in this study were 45 people, namely all laboratory staff. The results of the study based on data analysis using SPSS show that the training, documentation, and skills factors have a relationship with the laboratory staff's performance, and the most dominant factor affecting the staff's performance is skills. Therefore, suggestions for UPT leaders. The Regional Health Laboratory Center of Medan in order to give more serious attention to staff and to the deficiencies in the laboratory both in terms of infrastructure.